Analisis Kriminologi tentang Maraknya Judi Online dan Upaya Pemberantasannya melalui Pemblokiran Rekening Bank - Pawoko, Akbar Maulana; Kemala, Anyelir Puspa (Postulat, 2026)
This research analyzes the rise of online gambling practices in Indonesia from legal and criminological perspectives. The study aims to identify the underlying factors driving online gambling and to assess the effectiveness of bank account blocking as a law enforcement measure under Article 27 paragraph (2) of the ITE Law. Using a normative legal method combined with a criminological approach, the research examines statutory regulations and behavioral factors influencing perpetrators. The findings show that online gambling is driven by economic pressures, weak digital supervision, and easy access to gambling platforms. Although blocking bank accounts helps disrupt illegal financial flows, its effectiveness is limited by technical loopholes, rapid account switching, and weak coordination among law enforcement agencies, the Ministry of Communication and Information, and the Financial Services Authority (OJK). Therefore, a more integrated strategy is required, including stronger legal enforcement, improved technological supervision, enhanced inter-agency coordination, and public digital literacy programs to prevent online gambling